2004
DOI: 10.1136/tc.2003.004101
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco industry efforts to present ventilation as an alternative to smoke-free environments in North America

Abstract: Objective:To describe how the tobacco industry developed a network of consultants to promote ventilation as a “solution” to secondhand smoke (SHS) in the USA.Methods:Analysis of previously secret tobacco industry documents.Results:As with its other strategies to undermine the passage of clean indoor legislation and regulations, the tobacco industry used consultants who represented themselves as independent but who were promoting the industry’s ventilation “solution” strategies under close, but generally undisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 28 publications
0
81
0
3
Order By: Relevance
“…Like Smoking and Society, Clearing the Air was a compilation of articles, some from the same authors as Smoking and Society (Peter Berger and James Buchanan), as well as other authors who had tobacco industry ties, including Gray Robertson (Drope, Bialous, & Glantz, 2004), and Burt Neuborne (Shook Hardy & Bacon, 1991). Clearing the Air plainly says that it articulates the views of the tobacco industry, stating in the preface that the industry's views "are shouted down by antitobacco hotheads who have long since (if they ever had) any desire to debate the issues" (Tollison, 1988).…”
Section: Social Costs/social Values Book Projectsmentioning
confidence: 99%
“…Like Smoking and Society, Clearing the Air was a compilation of articles, some from the same authors as Smoking and Society (Peter Berger and James Buchanan), as well as other authors who had tobacco industry ties, including Gray Robertson (Drope, Bialous, & Glantz, 2004), and Burt Neuborne (Shook Hardy & Bacon, 1991). Clearing the Air plainly says that it articulates the views of the tobacco industry, stating in the preface that the industry's views "are shouted down by antitobacco hotheads who have long since (if they ever had) any desire to debate the issues" (Tollison, 1988).…”
Section: Social Costs/social Values Book Projectsmentioning
confidence: 99%
“…27 IFAQ studies were to provide a means for spreading the industry's message that secondhand smoke was an insignificant factor in air quality onboard aircraft. 19 Tobacco industry funded IFAQ studies, like those funded by governments and non-governmental organisations, clearly showed that secondhand smoke polluted aircraft in which smoking was permitted. 85 Four industry funded studies (including the SAS study) yielded similar concentrations of contaminants as did government and airline sponsored studies but offered different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco companies have frequently proposed air extraction and ventilation systems as adequate approaches to reduce or control SHS (Drope et al, 2004), despite repeated warnings by WHO regarding the ineffectiveness of such devices to eliminate SHS-associated health risks (WHO, 2007). We found the relative contribution of ventilation and air extraction systems to SHS reduction to be negligible compared with reductions attained from smoking bans.…”
Section: Discussionmentioning
confidence: 99%
“…While a vast body of literature has been dedicated to discussing mechanical systems versus smoking bans (AkbarKhanzadeh, 2003;Cenko, Pisaniello, & Esterman, 2004;Dearlove, Bialous, & Glantz, 2002;Drope et al, 2004;Samet et al, 2005;WHO, 2008), no systematic attempt has been conducted to quantify the effectiveness of each approach under nonexperimental conditions. In February 2008, a total smoking ban in all public places, including restaurants and bars, was enforced in Mexico City (Gaceta Oficial del Distrito Federal, 2008).…”
Section: Introductionmentioning
confidence: 99%